2022
DOI: 10.1007/s00268-022-06659-x
|View full text |Cite
|
Sign up to set email alerts
|

Severity of Illness Impacts Outcomes More than Admitting Service for Isolated Hip Fracture Patients

Abstract: Introduction Isolated hip fractures (IHF) are common injuries in the elderly. Controversy exists about which hospital service is best suited to manage these patients. We hypothesize that baseline patient severity of illness (SOI) score drives patient outcomes, not the hospital service managing these patients. Methods Retrospective review of all IHF patients from 2014 to 2018 at our Level 1 trauma center. Basic demographics were obtained. Patients were divided into service line they were admitted; surgical vs n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(7 citation statements)
references
References 30 publications
1
6
0
Order By: Relevance
“…A 2018 study by Lott et al [ 6 ] also concluded that patients with HF admitted to the medicine service had longer lengths of stay (LOS) and more complications compared to patients admitted to the trauma/orthopedic service. In contradiction to these conclusions, other studies determined that there were no differences in complication rates or LOS between the admitting services[ 8 , 10 ].…”
Section: Introductionmentioning
confidence: 96%
See 2 more Smart Citations
“…A 2018 study by Lott et al [ 6 ] also concluded that patients with HF admitted to the medicine service had longer lengths of stay (LOS) and more complications compared to patients admitted to the trauma/orthopedic service. In contradiction to these conclusions, other studies determined that there were no differences in complication rates or LOS between the admitting services[ 8 , 10 ].…”
Section: Introductionmentioning
confidence: 96%
“…Patients can be hospitalized for operative fixation of HF through different pathways, including trauma, orthopedic, and medicine admitting services[ 5 - 8 ]. In the studies comparing surgical vs nonsurgical pathways it has been reported that the admitting service can affect the management patterns and outcomes of patients with HF[ 5 , 6 , 9 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…12,13 For individuals with isolated hip fractures, the severity of illness (SOI) score may be a better indicator of outcomes. 14 Other scores, the Nottingham Hip Fracture Score and the orthopaedic version of the Physiologic and Operative Severity Score for the Enumeration of Mortality and Morbidity, and previously published risk prediction models could be time-consuming and inconvenient. [15][16][17] The red blood cell distribution width (RDW), which is the indication of size diversity among circulating red blood cells, has been as a biomarker reflecting systemic inflammation and malnutrition among elderly people.…”
Section: Introductionmentioning
confidence: 99%
“… 12 , 13 For individuals with isolated hip fractures, the severity of illness (SOI) score may be a better indicator of outcomes. 14 Other scores, the Nottingham Hip Fracture Score and the orthopaedic version of the Physiologic and Operative Severity Score for the Enumeration of Mortality and Morbidity, and previously published risk prediction models could be time‐consuming and inconvenient. 15 , 16 , 17 …”
Section: Introductionmentioning
confidence: 99%